The Influence of Electronic Word of Mouth, Accessibility, and Amenities on the Decision to Visit Banyak Island, Aceh Singkil - Helfina Meisarah; Imsar; Tri Inda Fadhila Rahma (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2025)
The present research endeavors to scrutinize the impact of Electronic Word of Mouth (E-WOM), spatial accessibility, and infrastructural amenities on tourists' behavioral intention to visit the maritime destination of Pulau Banyak, Aceh Singkil. This investigation is driven by empirical phenomena regarding suboptimal digital marketing orchestration, restricted geographical reachability, and the development of local support facilities. Employing a quantitative framework, this study utilized a survey technique involving 100 respondents with prior visitation experience. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach through SmartPLS 4.1. Empirical outcomes elucidate that E-WOM, logistical connectivity, and physical amenities simultaneously exert a positive and significant influence on visitors' destination choice. These findings formulate strategic imperatives for tourism authorities to intensify digital advocacy campaigns, improve transportation access, and optimize ancillary services to sustainably augment future tourist influx. Keywords: Electronic Word of Mouth, Accessibility, Amenities, Visitation Intent